Understanding FIDIC : the rainbow suite - Hughes, Kelvin (Engineering consultant) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Understanding FIDIC explains in simple and practical terms what is in fact a very complex range of international engineering and construction contracts"--
OCLC-licensed vendor bibliographic record.
Keywords: International Federation of Consulting Engineers; Construction contracts; Engineering contracts; Architectural contracts; Standardized terms of contract; LAW / Construction